Effects of step length and cadence on hip moment impulse in the frontal plane during the stance phase - Inai, Takuma (PeerJ, 2021)
BACKGROUND: An excessive daily cumulative hip moment in the frontal plane (determined as the product of hip moment impulse in the frontal plane during the stance phase and mean number of steps per day) is a risk factor for the progression of hip osteoarthritis. Moreover, walking speed and step length decrease, whereas cadence increases in patients with hip osteoarthritis. However, the effects of step length and cadence on hip moment impulse in the frontal plane during the stance phase are not known. Therefore, this study aimed to examine the effects of step length and cadence on hip moment impulse in the frontal plane during the stance phase. METHODS: We used a public dataset (kinetic and kinematic data) of over-ground walking and selected 31 participants randomly from the full dataset of 57 participants. The selected participants walked at a self-selected speed and repeated the exercise 15 times. We analyzed the data for all 15 trials for each participant. Multiple regression analysis was performed with the hip moment impulse in the frontal plane during the stance phase as the dependent variable and step length and cadence as independent variables. RESULTS: The adjusted R(2) in this model was 0.71 (p < 0.001). The standardized partial regression coefficients of step length and cadence were 0.63 (t = 5.24; p < 0.001) and −0.60 (t =  − 4.58; p < 0.001), respectively. CONCLUSIONS: Our results suggest that low cadence, not short step length, increases the hip moment impulse in the frontal plane. Our findings help understand the gait pattern with low hip moment impulse in the frontal plane.